Case–control study of anaemia among middle-aged and elderly women in three rural areas of China. Issue 8 (18th August 2014) - Song, Pengkun; Li, Lixiang; Man, Qingqing; Wang, Chunrong; Meng, Liping; Zhang, Jian
Abstract : Objectives: To propose a feasible suggestion to reduce the high prevalence of anaemia in middle-aged and elderly women by investigating risk factors, particularly nutritional factors, and analysing the effect on anaemia in three different rural areas of China. Design: A case–control study. Setting: Three counties of China. Participants: Women aged 50–75 years in the three counties. Main outcome measures: Adjusted OR (95% CI) of anaemia associated with diet, lifestyle and blood biochemical indices. Results: Compared with controls, women with anaemia had lower body mass index (22.1 (3.2) kg/m 2 vs 23.2 (3.5) kg/m 2 ; p<0.001), a higher experience of shortage of food (45.0% vs 36.5%; p<0.001), less soy food intake (0.5 (0.3, 26.7) g/day vs 5.6 (0.4, 27.8) g/day; p<0.048), lower serum iron (13.4 (5.4) μmol/L vs 16.4 (5.7) μmol/L; p<0.001), lower ferritin (109.6 (85.6) ng/mL vs 131.0 (92.0) ng/mL; p<0.001), lower transferrin saturation levels (22.5 (9.5)% vs 26.8 (9.6)%; p<0.001) and higher levels of free erythrocyte protoporphyrin (42.4 (21.2) μg/dL vs 39.6 (17.8) μg/dL; p<0.001). Anaemia was significantly associated with BMI(OR=0.90, 95% CI (0.87 to 0.92)), food shortage experience (OR=1.39, 95% CI (1.15 to 1.69)), total protein (OR=0.66, 95%CI (0.54 to 0.80)), Albumin (OR=0.72, 95%CI (0.59 to 0.87)) in univariate analysis. Multivariate analysis showed that body mass index, experience of food shortage, total protein and albumin were independently related to anaemia. Conclusions: Among middle-aged and elderly women in rural China, the nutrition status of anaemic cases is far below that of controls. Lower body mass index and a greater experience of food shortage are closely related to anaemia. Improving the blood protein status by consuming protein-sufficient foods such as soy food is a feasible approach for elderly anaemic women. Further research is needed on the effect of chronic inflammation and infectious disease on anaemia in elderly women in rural China.